Migration Italy : the art of talking back in a destination culture - Parati, Graziella, 1960- (Toronto : University of Toronto Press, 2005)
In terms of migration, Italy is often thought of as a source country - a place from which people came rather than one to which people go. However, in the past few decades, Italy has become a destination for many people from poor or war-torn countries seeking a better life in a stable environment. Graziella Parati's Migration Italy examines immigration to Italy in the past twenty years and the cultural hybridization that has occurred as a result.
1. Strategies of 'talking back' -- 2. Minor literature, 'minor Italy' -- 3. Cinema and migration : 'what' and 'who' is a migrant -- 4. The laws of migration
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: 20. století; imigrace -- Itálie -- 20. století; imigranti -- Itálie -- 20. století; italsky psaná literatura -- 20. století; menšinová literatura -- Itálie -- 20. století; literárněvědné rozbory; filmy -- Itálie -- 20. století; filmové náměty; immigration -- Italy -- 20th century; immigrants -- Italy -- 20th century; literature in Italian -- 20th century; minority literature -- Italy -- 20th century; literary criticism and history; films -- Italy -- 20th century; film themes; monografie; e-knihy online; monographs; e-books online